2012
DOI: 10.1186/1752-1947-6-272
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Incomplete transverse subtrochanteric femoral fracture with cortical thickening possibly secondary to risedronate use: a case report

Abstract: IntroductionOsteoporosis is an asymptomatic disease characterized by bone weakening and predisposition to fragility (insufficiency) fractures and can have devastating effects on individual life and great financial impact on the economy. Bisphosphonates are used worldwide for the primary and secondary prevention of osteoporotic fractures. However, increasing evidence raises concern that bisphosphonates can be associated with atypical fractures.Case presentationA 65-year-old Caucasian woman on long-term steroid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 8 publications
(11 reference statements)
0
3
0
Order By: Relevance
“…Now, with the 4-year results at hand, we no longer believe this. With the reported occasional occurrence of atypical subtrochanteric or diaphyseal femoral fracture in patients with long-term use of alendronate ( Sellmeyer 2010 ) and risedronate ( Alfahad et al 2012 ), the risk outweighs the merits of treatment in our opinion.…”
Section: Discussionmentioning
confidence: 80%
“…Now, with the 4-year results at hand, we no longer believe this. With the reported occasional occurrence of atypical subtrochanteric or diaphyseal femoral fracture in patients with long-term use of alendronate ( Sellmeyer 2010 ) and risedronate ( Alfahad et al 2012 ), the risk outweighs the merits of treatment in our opinion.…”
Section: Discussionmentioning
confidence: 80%
“…Many studies have reported that 99m Tc-HDP bone scans are useful for the detection of stress fracture, 16 17 18 19 and several studies used bone scans to diagnose AFF. 20 21 22 23 AFFs have a characteristic appearance and can be detected on bone scan. 22 Some focal thickenings of the femoral cortex, which are seen on plain radiographs, might be inactive scars after a stress reaction.…”
Section: Discussionmentioning
confidence: 99%
“…Atypical non‐traumatic femoral fractures have also been recognized as an important side effect of bisphosphonate use . These fractures affect the diaphyseal (subtrochanteric or shaft) part of the femur and, although involving a very small number, they are indeed associated with bisphosphonate use and have shown increased incidence over a 12‐year period , which is directly related to the longer duration of the drug therapy .…”
Section: Introductionmentioning
confidence: 99%